2018
DOI: 10.7454/irhs.v2i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Women in Middle Class Indonesia: Postfeminist Analysis of Women Wearing Veil in Depok (2010 – 2016)

Abstract: The presence of middle class is an urban phenomenon. Based on Asian Bank Development report, middle class has been risen in Asia since 1999 and Indonesia was among these countries. Indonesia is the most populated Muslim country in the world which is now facing the growth of middle class. In the other hand women and their bodies still be representatives of the nation economics’ face. Nowadays in the reformation era, many Indonesian women cover their body with Muslim clothes and veil. The number of middle class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Every person has a personal reason for wearing a hijab. Some of the reasons for Indonesian women wearing the veil are the awareness that at one time eventually she will wear the veil, the guilty feeling of getting older and still not wearing a veil, mother's coercion, wearing a veil is considered fashionable, a compulsory (religion's command), following ustadz (priest) advice, following friends who wearing a veil and being permitted wearing jilbab in office (Soekarba and Melati 2017). Besides, one wears the veil because of school regulations, spiritual experience, and motivation to find a religious husband (Bennett 2005).…”
Section: My Body Is My Rightmentioning
confidence: 99%
“…Every person has a personal reason for wearing a hijab. Some of the reasons for Indonesian women wearing the veil are the awareness that at one time eventually she will wear the veil, the guilty feeling of getting older and still not wearing a veil, mother's coercion, wearing a veil is considered fashionable, a compulsory (religion's command), following ustadz (priest) advice, following friends who wearing a veil and being permitted wearing jilbab in office (Soekarba and Melati 2017). Besides, one wears the veil because of school regulations, spiritual experience, and motivation to find a religious husband (Bennett 2005).…”
Section: My Body Is My Rightmentioning
confidence: 99%
“…After the regulation was introduced, women in headscarves and women adopting full-face veiling while dressed in the Middle Eastern style of Muslim clothing, namely the abaya , and men dressed in long white robes and white cotton pants became an increasingly common sight in Indonesian public spaces (Nisa 2013; Izharuddin 2015). Soekarba and Melati (2017) showed that veiling has become a trend among middle- and upper-class Indonesian Muslim women, who engage in veiling as an expression of both social class and religiosity as they believe that it is a religious doctrine that signifies their morality.…”
Section: Political Islam and Religious Conservatismmentioning
confidence: 99%
“…On the other hand, those women have conservative values such as marrying at an early age and a rigid gender role. This practice of wearing veil for Muslim women is not Islamization and post-Islamization movement but a pop culture expression to establish them as part of the Middleclass group [4].…”
Section: Introductionmentioning
confidence: 99%